2020
DOI: 10.3389/fmars.2020.00572
|View full text |Cite
|
Sign up to set email alerts
|

The Depleted Carbon Isotopic Signature of Nematodes and Harpacticoids and Their Place in Carbon Processing in Fish Farm Sediments

Abstract: Meiofauna δ 13 C Under Fish Farm sediment bacteria communities from the fish farm and reference site. The study demonstrated that fish farm-originating organic matter enters the meiofauna food chain, and that nematodes and harpacticoids use different food sources under the fish farm and at the reference site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…Increased deposition of organic matter on the seabed below fish cages (Kovac et al 2003, Lojen et al 2005 has been confirmed for our study area and negatively affects the sediment chemical properties and the abundance and structure of meiofauna (Grego et al 2009(Grego et al , 2020. The impact of aquaculture on microbes have been studied mainly in sediments, much less in the water column.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Increased deposition of organic matter on the seabed below fish cages (Kovac et al 2003, Lojen et al 2005 has been confirmed for our study area and negatively affects the sediment chemical properties and the abundance and structure of meiofauna (Grego et al 2009(Grego et al , 2020. The impact of aquaculture on microbes have been studied mainly in sediments, much less in the water column.…”
Section: Introductionsupporting
confidence: 74%
“…Uneaten food and faeces lead to the accumulation of a large amount of organic matter on the seabed below the cages in our study area (Lojen et al 2005) since the sedimentation rates in the vicinity of the fish cages were significantly higher (eight times higher) than background values for Piran Bay (Kovac et al 2003). Accumulation of organic and inorganic nutrients showed significant changes in redox potential and concentrations of chlorophyll a and phaeopigments in the sediment (Štrukelj 2008), as well as structure and abundance of meiofauna (Grego et al 2009(Grego et al , 2020. The negative influence of fish farm on the phytoplankton and bacterioplankton in immediate proximity was confirmed with in situ experiment with incubation in dialysis bags (Štrukelj 2008).…”
Section: Discussionmentioning
confidence: 77%
“…Other common methods used to track aquaculture wastes in marine systems and with potential application on benthic sessile taxa include fatty acids (FAs) and stable isotopes (SIs) turnovers. Aquaculture feeds are mostly made of terrestrial plants and consequently, typically contain high levels of terrestrial fatty acids (FAs) such as oleic acid 18:1 (n-9), linoleic acid 18:2 (n-6) and a-linolenic acid 18:3 (n-3)), and display a stable isotope signature depleted in d 13 C while enriched in d 15 N compared to marine organic compounds (Sarà et al, 2006;Yokoyama et al, 2006;Fernandez-Jover et al, 2011;Woodcock et al, 2017a;White et al, 2019;Woodcock et al, 2019;Grego et al, 2020;Sun et al, 2020). By feasting on aquaculture pellets and wastes, marine animals in close proximity to salmon farms may therefore exhibit altered FA and SI profiles that could be used to monitor the impact gradient of fish farming.…”
Section: Introductionmentioning
confidence: 99%